OPTIMALISASI PERAN EDUKASI DALAM PENCEGAHAN PERNIKAHAN DINI - Primadi, Novan Wahyu; Rangkuti, Fatmah (Inisiasi, 2025)
The fundamental purpose of marriage is to build a harmonious family that brings happiness to one another. To achieve this goal, several factors must be taken into account, including mental and physical maturity. Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 regarding marriage regulates the minimum age for marriage, which is 19 years for both men and women in Cangkring village, Jatiroro sub-district, Wonogiri regency. The phenomenon of early marriage remains high, with numerous negative impacts. This community service activity in the form of counseling was held on July 12, 2025. This activity is expected to benefit adolescents at risk of early marriage, enabling them to take preventative measures independently and further develop their potential in order to achieve a better life.